Repairable epoxy structural adhesive and preparation method thereof

By introducing special epoxy resins containing disulfide bonds and modified graphene into the epoxy structural adhesive, the problem of epoxy structural adhesives for power batteries is easily fatigued and failed under external forces, achieving self-healing and performance recovery, and significantly extending the service life.

CN119899615APending Publication Date: 2025-04-29GUANGZHOU JOINTAS CHEM
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510108044.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The epoxy structural glue used in existing power batteries is prone to internal microcracks under the action of external forces, resulting in fatigue failure, weak performance and insufficient service life, and cannot be repaired.

Method used

Special epoxy resins containing specific disulfide bonds and modified graphene are introduced as key components, in-situ repair is achieved through aromatic disulfide bond exchange reaction, and thermal conductivity and flame retardant properties are improved through modified graphene.

Benefits of technology

The epoxy structural adhesive is self-repaired by heating treatment after fatigue failure, and the mechanical properties are restored to more than 95% of the initial state, significantly extending the service life while maintaining high thermal conductivity, flame retardant and fluid properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005255977920000071
    Figure BDA0005255977920000071
  • Figure BDA0005255977920000081
    Figure BDA0005255977920000081
  • Figure BDA0005255977920000082
    Figure BDA0005255977920000082
Patent Text Reader

Abstract

The invention discloses a repairable epoxy structural adhesive and a preparation method thereof, and belongs to the field of chemical engineering, and the repairable epoxy structural adhesive is characterized in that specific disulfide bond-containing special resin and modified graphene are introduced into the product components to serve as key components, so that under the condition that high heat conduction efficiency, high flame retardance, high flowability and high mechanical strength are guaranteed, the repairable epoxy structural adhesive has a good heat conduction effect. When fatigue failure occurs due to external force, self-repairing can be achieved through heating treatment, and the service life is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of chemical industry, and in particular to a repairable epoxy structural adhesive and a preparation method thereof. Background Art

[0002] In addition to high bonding strength, epoxy structural adhesives for power batteries also need thermal conductivity, flame retardancy and durability. Compared with ordinary epoxy resins that do not have thermal conductivity and flame retardancy, epoxy resins for power batteries often need to be filled with a large amount of thermal conductive fillers and flame retardant additives, but these materials will cause the product's bonding performance to drop sharply, the internal toughness of the colloid is low, and microcracks are easily formed due to internal stress, resulting in a significant reduction in the tensile strength and mechanical properties of the product after a period of use, and poor durability.

[0003] Based on the specificity of the components of epoxy structural adhesives themselves, people try to adjust the type of materials or the formula ratio to improve the durability of the product. However, this approach may weaken other properties of the product and the degree of improvement in durability is limited. After the product fails due to fatigue caused by internal cracks, it still cannot be repaired. Summary of the invention

[0004] Based on the defects of the prior art, the purpose of the present invention is to provide a repairable epoxy structural adhesive. By introducing a specific disulfide bond-containing special resin and modified graphene as key components into the product components, while ensuring high thermal conductivity, high flame retardancy, high fluidity and high mechanical strength, when fatigue failure occurs due to external force, it can be self-repaired through heating treatment, thereby greatly extending the service life.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A repairable epoxy structural adhesive comprises a component A and a component B;

[0007] The A component comprises the following components in parts by weight:

[0008] 20-40 parts of epoxy resin, 30-60 parts of special epoxy resin, 5-10 parts of diluent, 5-10 parts of toughening agent, 1-5 parts of modified graphene, 0.5-2 parts of defoaming agent, 1-5 parts of thixotropic agent;

[0009] The B component includes the following components in parts by weight:

[0010] 30-50 parts of polyamide curing agent, 30-60 parts of amine curing agent, 5-15 parts of filler, 1-5 parts of modified graphene, 0.5-2 parts of defoaming agent, 1-5 parts of thixotropic agent;

[0011] The special epoxy resin is diphenyl diglycidyl disulfide ether;

[0012] The modified graphene is graphene grafted with phosphorus functional groups;

[0013] The mass ratio of the component A to the component B is 1:(0.8-1.2).

[0014] Preferably, the A component comprises the following components in parts by weight:

[0015] 30-35 parts of epoxy resin, 40-45 parts of special epoxy resin, 8-10 parts of diluent, 7-8 parts of toughening agent, 3-4 parts of modified graphene, 0.5-1 parts of defoaming agent, 1-3 parts of thixotropic agent;

[0016] The B component includes the following components in parts by weight:

[0017] 40-45 parts of polyamide curing agent, 40-45 parts of amine curing agent, 5-8 parts of filler, 2-4 parts of modified graphene, 0.5-1 part of defoaming agent, and 1-3 parts of thixotropic agent.

[0018] Epoxy structural adhesives used in power batteries and even new energy vehicles need to have basic application performance indicators including mechanical strength, thermal conductivity, and flame retardancy. However, due to the limitation of component formula, the existing epoxy structural adhesive products are prone to internal microcrack defects under the action of external forces, which ultimately lead to fatigue failure of the product, weakened performance, and insufficient service life. To this end, in the technical solution of the present invention, the inventor introduces a special epoxy resin containing disulfide bonds into the matrix resin. When this resin is combined with a polyamine curing agent, an aromatic disulfide bond exchange reaction can occur under heating conditions, thereby realizing the function of in-situ repair, so that even if the product fails due to fatigue, the mechanical properties including tensile strength can be restored to more than 95% of the initial state after repair, greatly extending the service life of the product; on the other hand, in the case of achieving self-repairability, the thermal conductivity and flame retardant components of the product also need to be specifically selected, otherwise the product may not be able to take into account the bonding strength, thermal conductivity and flame retardancy. In the product scheme of the present invention, both A and B components introduce a specific content of graphene modified with polar groups such as phosphorus-containing functional groups as a thermal conductive additive and a flame retardant additive. With the addition amount of the inorganic component, the product can ensure appropriate fluidity and bonding viscosity, and at the same time, the compatibility of the modified graphene with the epoxy resin is greatly improved, thereby achieving high dispersion uniformity in the resin, and the introduction of phosphorus-containing functional groups can greatly improve the flame retardant properties of the graphene component, and based on the conjugated structure of graphene, it can also exert excellent thermal conductivity, ultimately achieving excellent application effects of the product.

[0019] Preferably, the epoxy resin in the A component includes at least one of bisphenol A diglycidyl ether, bisphenol F diglycidyl ether and bisphenol S diglycidyl ether.

[0020] Preferably, the diphenyl diglycidyl disulfide ether can be a commercially available product or a homemade product.

[0021] More preferably, the diphenyl diglycidyl disulfide ether is prepared by the following method with reference to Composites Part B 199 (2020) 108278:

[0022] Dithiobisphenol A, potassium carbonate, N,N-dimethylformamide and epichlorohydrin are mixed, heated to 55-65° C. under a protective atmosphere and reacted for 12-24 hours to obtain intermediate 1;

[0023] After filtering and washing the intermediate 1, the intermediate 2 is obtained;

[0024] Anhydrous magnesium sulfate is added to the intermediate 2 and filtered. The obtained filtrate is decontaminated, recrystallized, and filtered to obtain diphenyl disulfide diglycidyl ether.

[0025] More preferably, the molar ratio of bisphenol disulfide, potassium carbonate, N,N-dimethylformamide and epichlorohydrin is 1: (0.05-0.15): (60-70): (7-10).

[0026] Preferably, the diluent in component A includes benzyl glycidyl ether, C 12-14 At least one of glycidyl ether, ethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and versatile glycidyl carbonate.

[0027] Preferably, the toughening agent in the component A includes at least one of carboxyl-terminated nitrile rubber modified epoxy resin, amino-terminated nitrile rubber modified epoxy resin, acrylic-rubber core-shell toughening agent, silicone rubber, and butyl rubber.

[0028] Preferably, the defoaming agent in the component A and / or the component B includes at least one of an organosilicon defoaming agent and a polyether defoaming agent.

[0029] Preferably, the thixotropic agent in component A and / or component B includes at least one of hydrophobic silica, organic bentonite and polyamide wax.

[0030] Preferably, the polyamide curing agent in the B component can be selected from common brands available on the market, such as Versamid 115 and Versamid 125 produced by Huntsman in the United States, and at least one of JH-5140, JH-5150, XH-463, XH-429 and XH-351 produced by Cadence.

[0031] Preferably, the amine curing agent in the B component includes at least one of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine and tetraethylenepentamine.

[0032] More preferably, the amine curing agent is diethylenetriamine.

[0033] The inventors have found through optimization that different amine curing agents have different effects during the reaction. When the above curing agents are selected, the self-healing effect of the product is better.

[0034] Preferably, the filler in the B component includes at least one of calcium carbonate, talc and silica powder, and the oil absorption value of the filler is in the range of 15 to 40 gmL / 100g.

[0035] Preferably, the modified graphene in the component A and / or component B is prepared by the following method:

[0036] Graphite and red phosphorus are mixed and ball-milled, the obtained powder is washed with anhydrous ethanol by reflux, washed with hydrochloric acid, filtered, and washed with water to obtain a filter cake;

[0037] The modified graphene is obtained by freeze-drying and grinding the filter cake.

[0038] The ball milling direct exfoliation method is used to directly prepare graphite and mixed red phosphorus into phosphorus-modified graphene, which can effectively improve the dispersibility of the group in the graphene product, thereby improving the dispersion performance of the overall product in various polar environments, and based on the setting of the group, the flame retardant performance of the product is significantly improved.

[0039] More preferably, the graphite is natural graphite with a mesh size of 80 to 150 meshes.

[0040] More preferably, the mass ratio of the graphite to red phosphorus is 1:(3-5).

[0041] More preferably, during the ball milling treatment of the graphite and red phosphorus, the rotation speed is 300-400 rpm and the time is 22-26 hours.

[0042] More preferably, the powder is washed with anhydrous ethanol under reflux for 22 to 26 hours.

[0043] More preferably, the concentration of the hydrochloric acid is 0.2-0.5 mol / L.

[0044] More preferably, the freeze-drying temperature is -80 to -150°C and the time is 46 to 50 hours.

[0045] More preferably, the grinding speed is 200-300 rpm and the grinding time is 1-2 h.

[0046] Another object of the present invention is to provide a method for preparing the repairable epoxy structural adhesive, comprising the following steps:

[0047] The epoxy resin, special epoxy resin, diluent, defoamer and toughening agent are mixed evenly, and then other components are added and dispersed evenly under vacuum to obtain component A;

[0048] The polyamide curing agent, the amine curing agent and the defoaming agent are mixed uniformly, and then other components are added and dispersed uniformly under vacuum to obtain component B.

[0049] The preparation method of the epoxy structural adhesive of the present invention has simple operation steps, low requirements on production conditions and settings, and can realize industrial production.

[0050] Another object of the present invention is to provide an application of the epoxy structural adhesive in the preparation of power battery components.

[0051] The epoxy structural adhesive of the present invention is based on specific component selection, and not only has high fluidity and is easy to use and process, but also has thermal conductivity and flame retardancy that meet application standards in the field of power batteries, and has excellent mechanical properties and mechanical strength. Even after fatigue failure after long-term use, it can achieve self-repair after simple heating treatment. The parts prepared therefrom have low replacement frequency and long service life.

[0052] The beneficial effect of the present invention is that the present invention provides a repairable epoxy structural adhesive. By introducing a specific special resin containing disulfide bonds and modified graphene as key components into the product components, while ensuring high thermal conductivity, high flame retardancy, high fluidity and high mechanical strength, when fatigue failure occurs due to external force, self-repair can be achieved through heating treatment, thereby greatly extending the service life. DETAILED DESCRIPTION

[0053] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.

[0054] Example 1

[0055] An embodiment of the repairable epoxy structural adhesive and a preparation method thereof according to the present invention comprises the following steps:

[0056] Mix epoxy resin, special epoxy resin, diluent, defoamer and toughening agent for 30 minutes, then add other components and disperse them in vacuum for 60 minutes until uniform, to obtain component A;

[0057] The polyamide curing agent, the amine curing agent and the defoaming agent were mixed for 30 minutes, and then other components were added and dispersed in a vacuum state for 60 minutes until uniform, to obtain component B;

[0058] The component A and the component B are packaged in a mass ratio of 1:1 to obtain the product.

[0059] The composition of the product components is shown in Table 1.

[0060] In the A component;

[0061] The epoxy resin is NPEL-128G produced by Nan Ya Kunshan, bisphenol A diglycidyl ether;

[0062] The special epoxy resin is homemade diphenyl diglycidyl disulfide ether, which is prepared by the following method with reference to Composites Part B199 (2020) 108278:

[0063] Dithiobisphenol A, potassium carbonate, N,N-dimethylformamide and epichlorohydrin were mixed in a 500 mL three-necked flask at a molar ratio of 1:0.1:65:8, and heated to 60° C. after nitrogen was introduced to react for 18 h to obtain intermediate 1;

[0064] The intermediate 1 was filtered, washed with 60 mL of deionized water, separated, and then washed with chloroform / hexane solution, and finally washed with 500 mL of deionized water, and then separated to obtain the intermediate 2;

[0065] Add an appropriate amount of anhydrous magnesium sulfate to the intermediate 2 and filter it with suction. Distill the filtrate to remove impurities, add an appropriate amount of methanol to recrystallize, and filter to obtain diphenyl disulfide diglycidyl ether.

[0066] The diluent was XY-207 prepared by Anhui Xinyuan;

[0067] The thixotropic agent is DM-20S produced by Tokuyama, Japan;

[0068] The toughening agent is 86840 produced by Shenzhen Jiadida;

[0069] The defoamer was BYK-530 produced by BYK Chemicals;

[0070] The modified graphene is a homemade product, which is prepared by the following method:

[0071] 100 mesh natural graphite and red phosphorus were mixed in a mass ratio of 1:4 and stainless steel beads with a diameter of 5 mm were added in a ball-to-material ratio of 100:1, and the mixture was ball-milled at a rate of 400 rpm for 24 hours. The obtained powder was reflux-washed with anhydrous ethanol in a Soxhlet extractor for 24 hours, then washed and filtered with 0.5 mol / L hydrochloric acid for 10 hours, and washed with water until the solution was neutral to obtain a filter cake;

[0072] The filter cake was freeze-dried at -120°C for 48 hours and ground in a grinder at 300 rpm for 2 hours to obtain the modified graphene;

[0073] In the component B,

[0074] The polyamide curing agent is Versamid 115 produced by Huntsman;

[0075] The amine curing agent is diethylenetriamine produced by Tosoh of Japan;

[0076] The filler is TN-M-3 produced by Zhejiang Tianshi, nano calcium carbonate, oil absorption value DOP 28~35mL / 100g;

[0077] The defoamer was BYK-530 produced by BYK Chemicals;

[0078] The thixotropic agent is DM-20S produced by Tokuyama, Japan;

[0079] The modified graphene originates from the same modified graphene in component A.

[0080] Embodiments 2 to 4

[0081] An embodiment of the repairable epoxy structural adhesive and the preparation method thereof of the present invention, wherein the preparation method is different from that of Embodiment 1 only in that the weight fractions of the components in Table 1 are different.

[0082] Example 5

[0083] An embodiment of the repairable epoxy structural adhesive and the preparation method thereof of the present invention, the preparation method is different from that of Example 1 only in that the epoxy resin used in component A is GEFR-170 bisphenol F epoxy resin produced by Hongchang Electronics.

[0084] Example 6

[0085] An embodiment of the repairable epoxy structural adhesive and the preparation method thereof of the present invention, the preparation method is different from that of embodiment 1 only in that the amine curing agent used in component B is ethylenediamine produced by Tosoh of Japan.

[0086] Example 7

[0087] An embodiment of the repairable epoxy structural adhesive and the preparation method thereof of the present invention, wherein the preparation method is different from that of embodiment 1 only in that the amine curing agent used in component B is tetraethylenetriamine produced by Tosoh of Japan.

[0088] Example 8

[0089] An embodiment of the repairable epoxy structural adhesive and the preparation method thereof of the present invention, wherein the preparation method is different from that of embodiment 1 only in that the amine curing agent used in component B is hexamethylenediamine produced by INVISTA of the United States.

[0090] Comparative Example 1

[0091] An embodiment of an epoxy structural adhesive and a preparation method thereof, wherein the preparation method is different from that of embodiment 1 only in that the modified graphene is prepared by the method described in paragraph

[0007] of the specification of CN104262588A:

[0092] 2g 100 mesh natural graphite, 1g potassium persulfate and 2g phosphorus pentoxide were mixed, 150g concentrated sulfuric acid was slowly added and stirred, the temperature was raised to 80°C for reaction for 6h, then the temperature was slowly lowered to room temperature, 500g water was added for dilution and the mixture was allowed to stand overnight, washed until neutral, and dried, then the obtained pre-oxidized graphite was added with 150g concentrated sulfuric acid in an ice bath and 8g potassium permanganate was added in batches, 250g water was slowly added for dilution, and finally 700g water and 30g 30% hydrogen peroxide were added to react until the solution turned bright yellow, and the solution was repeatedly washed with hydrochloric acid and water, dialyzed, and ball milled to obtain the modified graphene.

[0093] Comparative Example 2

[0094] An embodiment of an epoxy structural adhesive and a preparation method thereof, wherein the preparation method differs from that of embodiment 1 only in that the modified graphene in component A is replaced by an equal weight portion of red phosphorus, and the modified graphene in component B is replaced by XF021 graphene produced by Pioneer Nano.

[0095] Comparative Example 3

[0096] An embodiment of an epoxy structural adhesive and a preparation method thereof, wherein the preparation method is different from that of embodiment 1 only in that the special epoxy resin is replaced by AFG-90 epoxy resin produced by Shanghai Huayi.

[0097] Table 1

[0098]

[0099]

[0100] In order to verify the performance of the epoxy structural adhesive of the present invention, the products of each embodiment and comparative example were subjected to the following tests:

[0101] The specific method of the self-repair test is as follows: prepare three groups of 1BA type specimens according to GB / T 1040.2-2008 standard, with the number of specimens in each group being not less than 5. The first group of samples is pre-tested for initial tensile strength δ0, and the second and third groups of 1BA type specimens are repeatedly impacted 50-100 times with a force of 100N using an MTS CMT6000 universal material testing machine, and the microcracks are observed using a Keyence VHX-7000 ultra-depth microscope. If microcracks have occurred, the impact operation can be stopped, and then the second group of specimens is tested for tensile strength δ1 according to GB / T1040.2-2008 standard, and the third group of specimens is heated to 150°C and maintained for 6-12h, and then the tensile strength δ2 is measured using the same method, and the recovery rate of the performance after repair is calculated as R=δ2 / δ0×100%.

[0102] Table 3

[0103]

[0104]

[0105] It can be seen from the table that the viscosity of the epoxy structural adhesive prepared by the present invention can be maintained within the range of 50000~100000±2000cps, and the construction will not be affected by excessively high or low viscosity. At the same time, the shear strength on the aluminum substrate can reach 20MPa and above, the tensile strength can reach 40MPa and above, and the flame retardancy reaches UL94 V0, with excellent comprehensive performance. The most important thing is that the product can achieve self-repair after being subjected to external force and heated at 150°C, and the product performance can be restored to more than 85% of the initial state, and the service life is greatly extended. In contrast, the modified graphene used in the compounding of the product of Comparative Example 1 is the graphene oxide used in the existing partial improvement technology, but the product prepared by this component cannot achieve the expected flame retardant and thermal conductivity effects. In the product of Comparative Example 2, red phosphorus and graphene are not combined to prepare modified graphene, but red phosphorus with flame retardant effect and traditional unmodified graphene are used as components to prepare the product. Although the flame retardant performance of the product is better than that of the product of Comparative Example 1, the mechanical properties of the product cannot achieve the expected level. The special resin compounded with epoxy resin in the product of Comparative Example 3 is not the type of resin containing disulfide bonds described in the present invention, so the product does not have a self-repairing function. After being subjected to external force, the performance of the product decreases significantly, and it does not recover after heat treatment.

[0106] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A repairable epoxy structural adhesive, characterized in that: It includes component A and component B; The A component comprises the following components in parts by weight: 20-40 parts of epoxy resin, 30-60 parts of special epoxy resin, 5-10 parts of diluent, 5-10 parts of toughening agent, 1-5 parts of modified graphene, 0.5-2 parts of defoaming agent, 1-5 parts of thixotropic agent; The B component includes the following components in parts by weight: 30-50 parts of polyamide curing agent, 30-60 parts of amine curing agent, 5-15 parts of filler, 1-5 parts of modified graphene, 0.5-2 parts of defoaming agent, 1-5 parts of thixotropic agent; The special epoxy resin is diphenyl diglycidyl disulfide ether; The modified graphene is graphene grafted with phosphorus functional groups; The mass ratio of the component A to the component B is 1:(0.8-1.2).

2. The repairable epoxy structural adhesive according to claim 1, characterized in that: The epoxy resin in the component A includes at least one of bisphenol A diglycidyl ether, bisphenol F diglycidyl ether and bisphenol S diglycidyl ether.

3. The repairable epoxy structural adhesive according to claim 1, characterized in that: The diluent in component A includes benzyl glycidyl ether, C 12-14 At least one of glycidyl ether, ethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and versatile glycidyl carbonate.

4. The repairable epoxy structural adhesive according to claim 1, characterized in that: The toughening agent in the component A includes at least one of carboxyl-terminated nitrile rubber modified epoxy resin, amino-terminated nitrile rubber modified epoxy resin, acrylic-rubber core-shell toughening agent, silicone rubber, and butyl rubber.

5. The repairable epoxy structural adhesive according to claim 1, characterized in that: The defoaming agent in the component A and / or the component B includes at least one of an organosilicon defoaming agent and a polyether defoaming agent, and the thixotropic agent includes at least one of hydrophobic silica, organic bentonite, and polyamide wax.

6. The repairable epoxy structural adhesive according to claim 1, characterized in that: The amine curing agent in the B component includes at least one of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine and tetraethylenepentamine.

7. The repairable epoxy structural adhesive according to claim 1, characterized in that: The modified graphene in the A component and / or the B component is prepared by the following method: Graphite and red phosphorus are mixed and ball-milled, the obtained powder is washed with anhydrous ethanol by reflux, washed with hydrochloric acid, filtered, and washed with water to obtain a filter cake; The filter cake is freeze-dried and ground to obtain the modified graphene.

8. The repairable epoxy structural adhesive according to claim 7, characterized in that: The graphite is natural graphite with a mesh size of 80 to 150 meshes; the mass ratio of the graphite to red phosphorus is 1:(3 to 5).

9. The method for preparing the repairable epoxy structural adhesive according to any one of claims 1 to 8, characterized in that: The following steps are involved: The epoxy resin, special epoxy resin, diluent, defoamer and toughening agent are mixed evenly, and then other components are added and dispersed evenly under vacuum to obtain component A; The polyamide curing agent, the amine curing agent and the defoaming agent are mixed uniformly, and then other components are added and dispersed uniformly under vacuum to obtain component B.

10. Use of the epoxy structural adhesive according to any one of claims 1 to 8 in the preparation of power battery components.

Citation Information

Patent Citations

  • Graphene oxide-based curing agent as well as preparation and use thereof

    CN104262588A